2018
DOI: 10.1016/j.toxicon.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Citrus bioflavonoid, hesperetin, as inhibitor of two thrombin-like snake venom serine proteases isolated from Crotalus simus

Abstract: Around 5.5 million people suffer from snakebites per year, with about 400,000 cases with some type of sequelae, such as amputation, and 20,000 to 125,000 cases with the fatal end. Usually, the victim outcome depends on correct, agile and many times in situ intervention based on the proper identification of the snake venom type and its potential effects, among other factors. Therefore, knowledge on the snake venom composition and a research on inhibitors of snake venom target components might ameliorate envenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…Additionally, HSD and HST have been reported to inhibit intracellular replication of CHIKV [29]. Vander dos Santos and collaborators described inhibition of serine proteases by HST, isolated from snake venom [39], thereby demonstrating possible inhibitory potential of these molecules against different proteases.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, HSD and HST have been reported to inhibit intracellular replication of CHIKV [29]. Vander dos Santos and collaborators described inhibition of serine proteases by HST, isolated from snake venom [39], thereby demonstrating possible inhibitory potential of these molecules against different proteases.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the compound “AIPLAI” was isolated from the methanolic extract of the leaves of the plant Azadirachta indica inhibited venom PLA 2 in a dose-dependent manner, with reductions in activity ranging from 10% to 60% [ 33 ]. Flavonoids from citrus fruit extracts, particularly hesperetin, inhibit two SVSPs expressed by Crotalus simus [ 45 ]. Macrolobin A, derived from Pentaclethra macroloba extracts, reduced PI-SVMP and PIII-SVMP-induced proteolytic activity by up to 90% and 80%, respectively [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated the inhibition by phenolic compounds on other classes of toxins such as metalloproteases and serine proteases. [37,38] Enzymes belonging to the trypsin family such as snake venom metalloproteases (SVMPs), zinc-dependent enzymes, and snake venom serine proteases (SVSPs) are common in snakes from the families Viperidae and Colubridae. [21,39] These enzymes act in the degradation of substrates such as immunoglobulin, components of the cell membrane, and plasma proteins (eg, coagulation cascade).…”
Section: Discussionmentioning
confidence: 99%